Fastly match threat response policies based on interval decision diagram - Lingcui ZHANG; Fenghua LI; Liang FANG; Yunchuan GUO; Zifu LI (Tongxin xuebao)
Due to the inaccuracy of threat detection and the scale of response policies, it is very difficult to accurately select response policies.To address the above problem, fuzzy interval decision diagram to quickly match response policy was proposed.Firstly, the response policy was formally and fuzzily defined.Considering threat type, threat level, attack frequency and propagation mode, an algorithm with fuzzy operator was designed to construct interval decision diagram.Further, a fuzzy match algorithm was proposed to quickly select response policies.Experimental results show the efficiency of the proposed approach.